PELATIHAN PENYUSUNAN LAPORAN ARUS KAS - Hermaya Ompusunggu; Argo Putra Prima (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
Cash Flow Training is conducted to analyze the company's cash flow. This training was conducted for employees of the credit analysis section of Bank BNI. Cash flow analysis is carried out to analyze the cash activities of business entities that will apply for credit to Bank BNI so that bank analysts can determine the ability of prospective debtors to pay their debts. This is done starting from studying the company's cash flow to calculating the ratios related to cash flow. In this activity, participants were also asked to calculate the ratio and interpret the results of the ratio analysis that they calculated based on the questions given by the servant. This is done in groups and each group presents the results of their respective group cash flow analysis. With this training, it is expected to increase the knowledge of Bank employees in assessing and approving loans to be given to debtors.